9-3(x-4)=-6

Simple and best practice solution for 9-3(x-4)=-6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9-3(x-4)=-6 equation:


Simplifying
9 + -3(x + -4) = -6

Reorder the terms:
9 + -3(-4 + x) = -6
9 + (-4 * -3 + x * -3) = -6
9 + (12 + -3x) = -6

Combine like terms: 9 + 12 = 21
21 + -3x = -6

Solving
21 + -3x = -6

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-21' to each side of the equation.
21 + -21 + -3x = -6 + -21

Combine like terms: 21 + -21 = 0
0 + -3x = -6 + -21
-3x = -6 + -21

Combine like terms: -6 + -21 = -27
-3x = -27

Divide each side by '-3'.
x = 9

Simplifying
x = 9

See similar equations:

| 5c-2=18 | | 142=-16k+12 | | 2x+60=94 | | 4x=64+36 | | 4*(3.2+k)=8.2 | | 14t^2-8t=2t | | 5x-2(x-4)=19 | | -11=h+9-4 | | -8x+60=-4x+20 | | 9t^2=1 | | 4x^2-13x+8=-8x+7 | | 15(3+x)-6(3x-1)-7(1-x)=3(2-3x)-1 | | 4(3.2+k)=8.2 | | 3(x+3)+2(2x-4)=12(2x-7) | | k+(-13)=37 | | 300x+1590=x-818 | | -4x+21=2x+36 | | 6x-12x=0 | | 2x-10=24 | | 1-4xy+4x^2-y^2=0 | | 7x+10=6x | | -126-11x=78-5x | | 5x=3x+40 | | 2x-4=5x+40 | | 4+-9=-4t+7 | | (8+w)(5w-1)=0 | | -39-6x=66-13x | | 3x(11-7)+8= | | 10x-26=13x+61 | | -2x+60=-4x+20 | | 5x+3x+40=180 | | 12x+3=-14x+8 |

Equations solver categories